Understanding rabies persistence in low-density fox populations. Issue 3 (2nd October 2021) - Moran, E. Joe; Lecomte, Nicolas; Leighton, Patrick; Hurford, Amy
ABSTRACT: Arctic fox ( Vulpes lagopus ) and its tundra habitat are a unique system for the study of rabies virus epidemics. Contrary to theoretical calculations reporting a critical density (KT ) of approximately 1 fox/km 2 for rabies endemicity, arctic rabies persists at densities below this. The calculation of KT = 1 fox/km 2 assumes uniform fox density across the landscape and unrestricted mixing between susceptible and infected foxes. We hypothesize that spatial heterogeneity arising from resource distribution or social structure may result in regions where rabies is endemic, even though average fox densities at the regional or landscape-level are below KT . To expand upon the limited body of research surrounding arctic rabies persistence, we examine arctic rabies via a two-patch structure. We find that arctic rabies can persist in heterogeneous landscapes where the mean carrying capacity is below the threshold carrying capacity required for endemicity in homogeneous landscapes. Rabies endemicity in low-carrying capacity regions within heterogeneous landscapes is further facilitated by high transmission rates, potentially due to non-breeding foxes (i.e. floaters), and when between-patch movement is restricted to latent and infected foxes. Our results suggest that rabies may persist in heterogeneous landscapes when the mean carrying capacity is as low as 0.25 foxes/km 2 .